Time to sputum culture conversion as a predictor of cure in multidrug-resistant tuberculosis patients: a multicenter retrospective cohort study in Pakistan - Abdul Wahid; Nafees Ahmad; Fahad Saleem; Amjad Khan; Asad Khan; Faiz Ullah Khan; Farman Ullah Khan (Monaldi Archives for Chest Disease)
This study aimed to evaluate how the time to sputum culture conversion (SCC) predicts cure and to identify factors associated with delayed SCC and cure among multidrug-resistant tuberculosis (MDR-TB) patients receiving longer treatment regimens of 18-24 months. This multicenter retrospective cohort study was conducted at eight programmatic management units. A total of 462 patients with confirmed pulmonary MDR-TB were enrolled at eight PMDT sites between January 2017 and August 2018 with available treatment outcomes till 30th June, 2020. Survival analysis was done using the Kaplan-Meier curve, and Cox proportional hazards model and binary logistic regression were performed to determine factors associated with time to SCC and cure. Statistical significance was set at p<0.05. A total of 424/462 (91.8%) patients achieved SCC, with a cure rate of 75.5%. The mean time to SCC was 2.4 months (interquartile range = 1-3 months). Factors such as employment [hazard ratio (HR)=0.654, p=0.001], sputum smear grading score +2+3 (HR = 0.638, p=0.014), resistance to first-line drugs HREZ (HR=0.716, p=0.014), and resistance to second-line drugs, fluoroquinolones (HR=0.698, p≤0.001) were significantly associated with SCC. In the current study, the cure rate was 75.5% (349/462). In the binary logistic regression, month 1 [odds ratio (OR)=2.601, p≤0.001), month 2 (OR=3.14, p≤0.001), month 3 (OR=5.219, p≤0.001), month 4 (OR=6.788, p≤0.001), month 5 (OR=21.512, p≤0.001), and month 6 (OR=31.806, p≤0.001) had a statistically significant association with cure. In predicting cure, the overall sensitivities of SCC at 1, 2, 3, 4, 5, and 6 months were 37.2%, 64.1%, 85.9%, 91.1%, 97.4%, and 98.2%, respectively, and the specificities were 81.4%, 63.7%, 46.0%, 39.8%, 36.2%, and 35.3%, respectively. Interestingly, the combined sensitivity and specificity of SCC at 3 and 4 months in predicting cure were similar to those observed at 5 and 6 months.